Pengaruh Latihan Ergometer Rowing Machine Terhadap Peningkatan Power Endurance Pada Atlet Arung Jeram Faji Jawa Barat - Slamet Sumarno; Refki Sanjaya Pratama; Zulfikar Hamid Wada (JOURNAL SAINS STUDENT RESEARCH, 2026)
Whitewater rafting athletes require high physical capacity because competitions include several events (Sprint, Head to Head, Slalom, and Downriver Race) that demand a combination of strength and endurance to maintain paddling tempo, especially in the Sprint discipline, which is generally ±500 meters long (PB FAJI, 2019). Power endurance is a crucial component as it requires the ability to generate explosive and repeated power without quickly becoming fatigued (Widiowati, 2019). Training using a rowing ergometer can simulate rowing movements on land and provide measurable training feedback (Widiyani et al., 2022). To determine the effect of rowing ergometer training on improving power endurance in West Java FAJI whitewater rafting athletes. This was a quantitative study with a quasi-experimental pre-experimental one-group pre-test and post-test design. The subjects consisted of 12 athletes (6 males, 6 females) aged 20–30 years. The ergometer rowing machine training intervention was conducted 3 times/week for 6 weeks. Power endurance was measured using a 500-meter ergometer rowing test (time taken in seconds). Data analysis included the Shapiro–Wilk normality test and the Paired Sample t-test. The average time decreased from 161.83 seconds (pre-test) to 143.58 seconds (post-test), a difference of 18.25 seconds. The data were normally distributed (p>0.05). The Paired Sample t-test showed a significant difference with p < 0.001, indicating that ergometer rowing machine training had a significant effect on increasing power endurance. Ergometer rowing machine training effectively increased the power endurance of West Java FAJI whitewater rafting athletes, as indicated by a significant decrease in 500-meter completion time.